Inducible developmental reprogramming redefines commitment to sexual development in the malaria parasite Plasmodium berghei - Kent, Robyn S (Nat Microbiol, 2018)
During malaria infection, Plasmodium spp. parasites are cyclically invading red blood cells (RBCs) where they can follow two different developmental pathways: replicate asexually to sustain the infection or differentiate into gametocytes - sexual stages which can be taken by a mosquito ultimately leading to disease transmission. Despite its key importance for malaria control, the process of gametocytogenesis remains poorly understood, partially due to the difficulty of generating high numbers of sexually committed parasites in laboratory conditions1. Recently an apicomplexa-specific transcription factor (AP2-G) was identified as necessary for gametocyte production in multiple Plasmodium species2,3.and suggested to be an epigenetically regulated master switch initiating gametocytogenesis4,5. Here we show that in a rodent malaria parasite Plasmodium berghei conditional overexpression of AP2-G can be used to synchronously convert the great majority of the population into fertile gametocytes. This discovery allowed us to redefine the time frame of sexual commitment, identify a number of putative AP2-G targets and chart the sequence of transcriptional changes through the gametocyte development including the observation that gender partitioned transcription within 6 h of induction. These data provide entry points for further detailed characterization of the key process required for malaria transmission.